GAYA ELIQUTARIUM WAKIL GUBERNUR PROVINSI DKI JAKARTA – DJAROT SAIFUL HIDAYAT DALAM MEWUJUDKAN GOOD GOVERNANCE PADA KEPEMIMPINAN DEMOKRATIS DI PEMERINTAH PROVINSI DKI JAKARTA - Nadia Chandrawita (Universitas Mercu Buana, 2017)
Every human being has a different style of communicating. The communication style can follow the conditions and situations so that each individual can have several kinds of communication style. The quiet communication style, becomes the prominent characteristic of Djarot Saiful Hidayat (DJS), Vice Governor of DKI Jakarta Province, and this draws public attention to talk about. The purpose of this study is to determine the communication style and leadership style of Vice Governor of DKI Jakarta Province - Djarot Saiful Hidayat in forming Good Governance in the Provincial Government of DKI Jakarta. This research method is case study with qualitative research approach. This research is conducted with qualitative approach (approach) is approach that aims to explore a symptom. For data validity, researchers used triangulation of data. Triangulation, in data collection techniques, triangulation is defined as data collection techniques that combine from various data collection techniques and data sources that already exist. The research finds that, Djarot Saiful Hidayat apply The Equalitarian Style in communicating, that is two-way communication style based on equality aspect. The leadership style applied by Djarot Saiful Hidayat is a democratic type of leader, which is willing to cooperate to achieve the predetermined objectives by sharing activities that have been determined together between leaders and subordinates, in order to implement good governance.Keywords: Communication Styles, Leadership Style, Good Corporate Governance